Intramuscular (Infiltrating) Lipoma of the Floor of the Mouth - Ben-Zion Joshua; Lipa Bodner; Ruthy Shaco-Levy (Case Reports in Medicine)
Lipoma is a very common soft tissue neoplasm, but only infrequently found in the oral region. Intramuscular lipoma (IML) is a relatively common variant of lipoma. The most common site for IML is the large muscles of the extremities, and it is quite rare in the oral cavity. A case of IML affecting the floor of the mouth/tongue of a 42-year-old female is described. The patient presented with a 4 cm diameter yellow mass in the right side of the sublingual area. Axial and coronal magnetic resonance imaging demonstrated its infiltrating nature that can be distinguished from the ordinary well-encapsulated lesion. The lesion was excised with adequate surgical margins. Histopathologically, the lesion was composed of mature adipose tissue that infiltrated the muscle in a diffuse manner. No lipoblasts, atypical cells, or high mitotic index were found. There was no evidence of recurrence two years postoperatively. Review of the literature yielded that IML occurring in the sublingual region is extremely rare.